When work bothers your mind: a diary study on the relationship of German teachers’ work-related rumination with fatigue - Weiher, Gerald M.; Varol, Yasemin Z.; Horz, Holger (Frontiers in Education, 2023)
This study investigated the association of school attendance restrictions in the early stages of the coronavirus disease pandemic with teacher-specific workload, and work-related rumination of teachers in Germany. Deduced from the effort-recovery model, that assumes that work might lead to strain reactions, making recovery necessary to avoid long-term health impairments, fatigue and positive and negative contents of work-related rumination in nonwork time were investigated in a five-day diary study with three measurement points per day. A total of 1697 daily measures of 174 teachers were gathered for over three consecutive workdays and the weekend. Only those days were included in which the teachers worked. Multilevel structural equation modeling revealed that teachers during school restrictions showed lower teacher-specific workload, which was associated with lower levels of affective rumination and problem-solving pondering. The effect on fatigue was mediated only by affective rumination such that a higher affective rumination was related to a higher fatigue level on the between and within-level. There was a significant three-path mediation from group belongingness over teacher-specific workload to affective rumination and fatigue. Problem-solving pondering did not affect fatigue level. The present study provides evidence of the association of COVID-19 restrictions with teacher-specific workload and the importance of differentiating the facets of work-related rumination.